Offshore wind energy integration in the European power system - Peña, Juan Julián Peiró (My University, 2008)
In Europe there are large plans for offshore wind energy and especially the North Sea region are of interest. This large scale integration of wind power generation in power systems presents several problems that must be confronted for a better development. Some of them are generation scheduling, load-frequency control, reactive power-voltage control and power system stability. In this thesis, the stability of the future North Sea electric grid in the presence of large off-shore wind farms will be studied. A test system is modeled using the simulation tool PSS/E. The first step is to estimate the configuration and parameters of the offshore wind network connected to land. Results from the static and dynamic simulations of the model are analyzed to discuss how the power balance and system reliability with the increased wind power penetration can be maintained. The new technology based in transistors HVDC Light is taken in consideration for connecting islanded systems to AC grid systems when connection points are far away. It is found that a scenario with more than 6% of offshore wind power supply does not serve grid connection requirements in UK. This value increases up to 12% in Germany in part because of the offshore platforms network. Therefore some grid reinforcements are needed to carry out the goal for European offshore wind energy in the North Sea, 10 GW of installed power in 2020. A 6% offshore wind integration scenario in the North Sea is analyzed interconnecting both offshore areas with DC cables and simulating some contingencies. It is concluded that the HVDC link does not endanger the system stability but improves it in some cases, i.e., critical fault clearing time.
Keywords: Elkraftteknik; Electric power engineering